IMPLEMENTASI PERMAINAN JEOPARDY UNTUK MENINGKATKAN KETERAMPILAN GRAMMAR - Deborah Tirtania Chrisna Pake Seko; Aisyah Nurdianingsih P.A. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The lack of students’ understanding on the use of tenses becoming the main reason of Jeopardy game implementation to enhance students’ grammar skill. This study is a class action research which aims to investigate the effectivity of Jeopardy game implementation toward students’ grammar skill especially on the use of simple past tense and past continuous tense. The subject of this research is 36 students at tenth grade of SMAN 1 Kota Kupang. The data was analyzed by conducting comparative description in which the researchers compared the results of both pre-test and post-test of first and second cycle. The results showed that Jeopardy impact effectively in creating positive and exciting learning environment as well as enhancing students’ comprehension and skill of simple past tense and past continuous tense.